Apremilast Regulates the Teff/Treg Balance to Ameliorate Uveitis via PI3K/AKT/FoxO1 Signaling Pathway - Chen, Yuxi; Li, Zhuang; Li, He; Su, Wenru; Xie, Yanyan; Pan, Yuan; Chen, Xiaoqing; Liang, Dan (Frontiers in Immunology, 2020)
Autoimmune uveitis(AU), being one of the sight-threatening ocular inflammatory disorders, has been widely regarded by ophthalmologists and immunologists as a great challenge. Apremilast, a phosphodiesterase-4 inhibitor (PDE4i), which was approved by the US Food and Drug Administration(FDA) for the treatment of active psoriatic arthritis in 2014, has been attracting researchers, who are exploring its efficiency and mechanism on uveitis. In this study, we used an experimental autoimmune uveitis(EAU), a representative model for human AU, to investigate the effect of apremilast on regulating anti-inflammatory mediators. Our study demonstrated that apremilast treatment resulted in a decrease in vascular leakage, macular edema, and inflammatory cells infiltration in the retina, corresponding to decreased clinical and pathological scores. Specifically, apremilast decreased the proportion and population of Th17 cells and increased the proportion and population of T regulatory (Treg) cells. Mechanistical-ly, apremilast may regulate Th17 and Treg by inhibiting the phosphorylation of the phosphoinositide 3-kinase (PI3K)/ protein kinase B(AKT)/ Forkhead box O1(FoxO1) signal pathway. These findings suggested that apremilast alleviated EAU by regulating Th17 and Treg through the PI3K/AKT/FoxO1 pathway.